Legal Consequences on the Loss of Collateral at Setia Budi Islamic Pawnshop Medan City from the Perspective of Maslahah Mursalah - Azzahra, Vita; Tarigan, Tetty Marlina (University of Darusssalam Gontor, 2024)
The loss of collateral items in Islamic pawnshop raises several legal consequences that need to be managed to remain it in accordance with sharia principles and public welfare. This research aims to examine the legal consequences on the loss of collateral at Setia Budi Islamic pawnshop Medan city from the perspective of maslahah mursalah. This research used qualitative method, field research, with empirical research. The results, the loss of collateral items in Islamic pawnshop can lead to legal disputes between the pawnshop and customers, and the application of maslahah mursalah principles can provide solutions to these disputes. The application of maslahah includes the protection of customers' property rights, maintaining the reputation and credibility of Islamic pawnshop, and enhancing public trust. This research shows that the responsibility provided by Setia Budi Islamic pawnshop Medan city is in accordance with Islamic law, which states that the liability in Islamic law is the lowest price or the debt price. Meanwhile, the Islamic pawnshop provides compensation of 5% of the estimated value of the item, not from the loan amount, so the compensation given by Islamic pawnshop is sufficient to cover the losses experienced by the customers. This shows that Setia Budi Islamic pawnshop Medan city are fully responsible for the collateral entrusted to Islamic pawnshop. Thus, this can provide a sense of security and comfort to customers who wish to use the services available at Islamic pawnshop.